A wikipédia no Ensino Superior online: que perceções? - Pestana, Filomena (2021)
Wikipedia can be said to have a ubiquitous character, namely taking into account that whenever we use an online search engine the results first presented come from it. And, if we consider the student population, it has been observed that Wikipedia is one of their main sources of research. Aware of the potential of Wikipedia in educational contexts, we have been characterizing it, in previous studies, as an open educational resource. Focusing on Wikipedia, we asked about possibilities of curricular integration in Online Higher Education, ultimately aiming at contributing to the Wikipedia University Program in Portugal, which had not been done before. Methodologically, the study assumes a qualitative and quantitative paradigm. The data analyzed in this text was collected by a survey made available at the beginning and at the end of the Course Unit. The results allow us to conclude that, in general, consensus was recognized, from which we can infer that there was, at first, an openness on the part of the students so that the curricular integration of Wikipedia would be welcomed. In the second moment, this was confirmed, by the involvement of the students who participated in the study, that is, their positive perception was reinforced.